Oxidation of ethanol and its derivatives on well defined pt single crystal electrodes vicinal to pt(111): a comparative study - Aran-Ais, Rosa Maria; Santos, Nathalia Abe [UNESP]; Villullas, Hebe de Las Mercedes [UNESP]; Feliu, Juan Miguel (The Electrochemical Society, 2013)
The oxidation of ethanol (EtOH) at Pt(111) electrodes is dominated by the 4e path leading to acetic acid. The inclusion of surface defects such as those present on stepped surfaces leads to an increase of the reactivity towards the most desirable 12e path leading to CO2 as final product. This path is also favored when the methyl group is more oxidized, as in the case of ethylene glycol (EG) that spontaneously decomposes to CO on Pt(111) electrodes, thus showing a more effective breaking of the C-C bond. Some trends in reactivity can be envisaged when other derivative molecules are compared at well-ordered electrodes. This strategy was used in the past, but the improvement in the electrode pretreatment and the overall information available on the subject suggest that relevant information is still missing.